Hot injection synthesis and characterization of copper antimony selenide non-canonical nanomaterials toward earth-abundant renewable energy conversion - Agocs, Daniel B., author; Prieto, Amy L., advisor; Buchanan, Kristen, committee member; Sambur, Justin, committee member; Sites, James R., committee member; Van Orden, Alan, committee member (Colorado State University. Libraries, 2018)
Renewable and carbon-free energy generation has become a critically important field as the global population continues to increase. Further, the ample supply afforded by natural resources such as sunlight and geothermal heat are attractive options that can be harnessed using technologies like photovoltaics and thermoelectrics. There is a growing interest in searching for novel materials that exhibit high efficiencies in these devices, ideally composed of earth abundant, non-toxic materials. This search is aided by theory, which has identified several families of compounds with interesting structure types that may exhibit properties amenable to incorporation in high efficiency devices. However, many of these materials have not yet been thoroughly evaluated for photovoltaics or thermoelectrics. This dissertation is focused on developing the synthesis and describing the basic characterization of nanoparticles of members of the compounds in the Cu-Sb-Se series, of which syntheses have been developed for Cu3SbSe4 and Cu3SbSe3 and are described in this dissertation. Herein, we describe a hot-injection route for the formation of Cu3SbSe4 and Cu3SbSe3 nanocrystals. In order to place this work in context, the first chapter of this dissertation provides a detailed summary of the literature investigating the Cu-Sb-Se family of compounds. Here, the highest thermoelectric efficiencies have been achieved for Cu3SbSe4 while Cu3SbSe3 is not yet comparable thermoelectrically to Cu3SbSe4 nor as efficient as the photovoltaic material CuSbSe2. The second chapter details the development of a hot injection synthesis of Cu3SbSe4 nanocrystals. In order for these materials to be applied as electronic materials in real devices, their stability and function under ambient conditions is of interest. Therefore, we studied the changes in electronic conductivity as a function of exposure to atmosphere. The conductivity increase was attributed to a hole mobility increase, and this was further correlated to structural oxidations. Chapter 3 details development of a synthesis for phase-pure Cu3SbSe3 nanodiscs. This material has become of interest recently for photovoltaic applications due to its acceptable band gap for solar absorption. While the synthesis of nanoscale Cu3SbSe3 has been reported, these results have not been reproduced, and property measurements among these limited works vary. Therefore, a robust synthesis was developed and initial optical and photoelectrochemical properties were measured and are reported in this dissertation that demonstrate photoactivity in thin films of the Cu3SbSe3 nanodiscs. In the fourth chapter, a more vigorous exploration of the nanodisc morphology observed in Cu3SbSe3 is reported. As a degree of self-assembly is observed in stacks of the nanodiscs, the morphology is investigated to understand how tuning nanocrystal morphology, size, and surface might affect the resulting particle interactions. To this end, a double injection synthesis was developed wherein the products exhibit optoelectronic properties similar to those of the original single injection reaction. Chapter 5 entails the electrochemical investigation of the copper antimony selenide nanostructures. Electrochemical measurements to experimentally elucidate the electronic structure are reported, and a photovoltaic architecture is proposed for a Cu3SbSe3-absorber layer device. Further, the presence of a thiol has been demonstrated to be critical to not only morphology within the Cu3SbSe3 synthesis but also the product phase formation. Therefore, initial measurements and challenges with in-situ electrochemical exploration of precursor reactivity are reported. Finally, chapter 6 briefly emphasizes the major findings within this dissertation. The experimental results for both Cu3SbSe4 and Cu3SbSe3 syntheses are reiterated. Further, additional directions for future work with this system are suggested. These primarily focus on fabrication of a Cu3SbSe3 photovoltaic cell to begin understanding photogenerated carrier transport. This can be extended through applying knowledge gained by understanding disc stacking to improve film deposition and electronic properties within Cu3SbSe3 materials. Finally, development of an electrochemical measurement system for use in oleylamine media would allow a new perspective on investigation of colloidal nanocrystalline formation. These proposed experiments would contribute to their respective fields in the broader context of expanding search criteria for novel photovoltaic materials, addressing the challenge of grain boundary recombination sites in photovoltaic nanocrystals, and providing tools for exploring nanoparticle synthesis.